Analisa Pengaruh Gaya Kepemimpinan Dan Komunikasi Terhadap Kinerja Pegawai Pada Dinas Perhubungan Kabupaten Aceh Tenggara - Ardi Hirmansah; Yunita Althin Natanael (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
The Department of Transportation has the task of carrying out government duties in the field of excellence in creating orderly, smooth, safe, and comfortable traffic. This study aims to determine the extent of the analysis of the influence of leadership style and communication in an effort to improve employee performance at the Southeast Aceh District Transportation Service. This research was conducted at the Southeast Aceh Regency Transportation Service which is located on Jalan T. Bedus Samad, Babussalam District, Southeast Aceh Regency. The data analysis used by the author is qualitative data analysis. Qualitative analysis is an analytical effort that is carried out without using calculations but with our thoughts or opinions that can support the analysis in this study.Democratic leadership and good communication have a positive effect, meaning that democratic leadership style is improved, employee performance increases and democratic leadership style has a significant effect on employee performance, showing leadership style has a significant effect on employee performance, leadership style has a role in improving employee performance. in other words that leadership style and communication is the cause of the increase in employee performance